The Effectiveness of Complete Systemic Land Registration (PTSL) Program by the Land Office towards Increasing Ownership of Certificate of Land Rights in Malang District - Musleh Harry (Budapest International Research and Critics University, 2022)
The effectiveness of the complete systematic land registration program to increase the ownership of land rights certificates at the Malang Regency land office has not been effective. The Covid-19 pandemic had an impact on the target of issuing a Complete Systematic Land Registration certificate in Malang Regency. Impact of Covid 19, In 2020, the target is only 4,675 plots of land by pre-antecedent, only 50 percent of land in Malang Regency has a certificate. Farmers who do not have a field certificate are 651 fields. Still less than 650 thousand. The inhibiting factors for the complete systematic land registration program to increase the ownership of land rights certificates by the Malang Regency land office include (1) the level of community education (2) PTSL applicants are difficult to attend during measurement activities (3) Completeness of administrative requirements (4) Still lacking Coordination (5) Lack of Community Interest and Discipline of Malang Regency and (6) Geographical Condition of Malang Regency. Efforts made by the land office of Malang Regency in streamlining the complete systematic land registration program towards increasing ownership of land rights certificates are (1) Coordinating the Land Office with the village/kelurahan government (2) Increasing Outreach To Attract Enthusiastic Citizens and (3) Increasing Quality of Facilities and Infrastructure.